Pembuktian dan Perlindungan Hukum terhadap Korban Perselingkuhan dalam Sengketa Harta Bersama - Faizal, Nadya; Arnita Sari, Dewi (IAIN BONE, 2024)
This article systematically examines the process of proving infidelity and the forms of legal protection available to victims in disputes over the division of marital property following divorce in Indonesia. The research employs a normative juridical method and a comparative legal approach to analyze positive legal provisions, court decisions, and the practices of religious courts related to divorce cases caused by infidelity. The findings indicate that although infidelity is recognized as a legitimate ground for divorce under Indonesian law, the legal system does not yet provide adequate protection for the victims in the division of marital assets. Judges continue to divide property proportionally without considering the moral wrongdoing of the unfaithful party. Meanwhile, in jurisdictions such as Malaysia and several U.S. states, mechanisms for compensation or limitations on property rights for the at-fault party exist. This article recommends a reform of Indonesian marital law to be more responsive to victims of infidelity, including strengthening the recognition of digital evidence, drafting prenuptial agreements, and providing compensation in the form of mut’ah or unequal division of assets. These findings are expected to enrich the discourse on substantive justice in Indonesia’s family law system.